International open-label studies to assess the efficacy and safety of single-pill amlodipine/atorvastatin in attaining blood pressure and lipid targets recommended by country-specific guidelines: the JEWEL programme. - Richard Hobbs, F; Gensini, G; John Mancini, G; Manolis, A; Bauer, B; Genest, J; Feldman, R; Harvey, P; Jenssen, T; da Silva, P (2009)
BACKGROUND: Single-pill amlodipine/atorvastatin targets the two most common modifiable cardiovascular risk factors, hypertension and dyslipidaemia. We evaluated the clinical utility of this single pill to help patients across Europe and Canada achieve country-specific targets for blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C). DESIGN: Two 16-week, open-label studies conducted in 122 study centres across the United Kingdom and Canada (JEWEL 1) and 113 centres across 11 European countries (JEWEL 2). METHODS: Patients with uncontrolled BP and controlled/uncontrolled LDL-C qualifying for treatment according to local governing guidelines were administered single-pill amlodipine/atorvastatin with appropriate lifestyle modification. Eight dosages of amlodipine/atorvastatin (5/10-10/80 mg) were titrated to achieve country-specific BP and LDL-C targets. The primary outcome was the percentage of patients reaching country-specific BP and LDL-C targets in 16 weeks. RESULTS: Among 2245 patients enrolled in the studies (JEWEL 1, n = 1138; JEWEL 2, n = 1107), 62.9% in JEWEL 1 and 50.6% in JEWEL 2 achieved both country-specific BP and LDL-C goals. BP was reduced by 20.4/10.7 and 21.8/12.6 mmHg in JEWEL 1 and JEWEL 2, respectively, and reductions in LDL-C were 0.90 mmol/l (34.8 mg/dl) and 1.09 mmol/l (42.2 mg/dl), respectively. The most common adverse events were peripheral oedema (11.0%), joint swelling (2.9%) and headache (2.9%), of which, only oedema was linked to study treatment. CONCLUSION: Single-pill amlodipine/atorvastatin is an effective and well-tolerated treatment, which in a real-world setting helped more than half of the patients achieve both BP and LDL-C targets as recommended by local guidelines. Although fewer patients met their goals in JEWEL 2 than JEWEL 1, reductions in BP and LDL-C were slightly greater in JEWEL 2, suggesting that the observed differences are likely because of more stringent targets in Europe than in the UK/Canada.